2010
DOI: 10.1016/j.rmed.2009.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Increased oral nitric oxide in obstructive sleep apnoea

Abstract: The finding that oral NO is increased in OSA and is related to upper airway obstructive episodes and to hypoxemia severity, strengthens the clinical and pathogenic role of oral inflammation in OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
(9 reference statements)
2
27
0
Order By: Relevance
“…These high nNO levels were not correlated with the severity of the disease defined by the PSG results and indeed were similar also in snoring children who did not suffer from sleep apnea. Our results are in agreement with previous studies in adult patients that showed increased nNO levels, eNO, and even oral NO in OSA [31,37,38]. NO is a marker of inflammation, especially allergic inflammation, and its production is increased during inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…These high nNO levels were not correlated with the severity of the disease defined by the PSG results and indeed were similar also in snoring children who did not suffer from sleep apnea. Our results are in agreement with previous studies in adult patients that showed increased nNO levels, eNO, and even oral NO in OSA [31,37,38]. NO is a marker of inflammation, especially allergic inflammation, and its production is increased during inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that only 0% and 5% O 2 , but not 10% O 2 , AIH potentiated the apneic response and LVCF sensitivity to capsaicin suggests that this sensitizing effect depends on the severity of AIH. These findings agree with observations that airway inflammation, such as oxidative stress in patients with OSA is positively related to disease severity (14). In our preliminary study, we found that exposure to 10% O 2 AIH for a longer duration (20 episodes) may induce LVCF hypersensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…4,[23][24] The results we observed in our study are consistent with the current evidence showing elevated cytokines and inflammatory markers in exhaled breath as well as upper airway tissues of OSA patients. 4,[9][10][11][12][13][14][15][16][17]23,[25][26][27][28] Salerno et al and Devouassoux et al detected increased neutrophils and reduced macrophages in the induced sputum of OSA patients. 27,28 The latter study also observed a concurrent higher interleukin-8 concentration in the induced sputum specimen of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Prior studies that have evaluated the FENO levels in OSA have shown inconsistent results. [7][8][9][10][11][12][13][14][15][16][17] Specifi cally, studies have shown no difference, 8,10 mild increase, 13 or signifi cant increases in FENO 7,9,11,12,14,16,17 compared to controls. Post-vs. pre-sleep FENO was signifi cantly increased in one study 7 but unchanged in another.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation